Dinamika Perkembangan Sosial Anak dan Remaja: Peran Pola Asuh, Teman Sebaya, Lingkungan, dan Media Sosial Di Era Digital: ` - maksum; Musripah (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2026)
This study discusses the social-emotional development of children and adolescents, which is influenced by various factors, particularly parenting styles, peer interactions, school environments, and social media. This topic is important because today’s young generation grows up in two environments simultaneously: the real world and the digital world. The study uses a literature review method by examining relevant publications from the past five years. The analysis shows that authoritative parenting, positive peer relationships, supportive school and community environments, and wise use of social media play important roles in shaping their social-emotional skills. Another finding highlights that parents’ digital literacy is still rarely discussed, even though it is crucial for guiding children in using technology. Overall, social-emotional development is formed through the interaction of multiple factors; therefore, collaboration among families, schools, and the digital environment is needed to support healthy growth and development in children.